Relationship of Food Leftover with Covid-19 Inpatients Recovery Speed in Palembang Indonesia - Devi Eryanti; Chairil Anwar; Yuanita Windusari; Ramzi Amin; Ahmad Ghiffari (HM Publisher, 2021)
Background : Hospital nutrition services support the patient's recovery process, which the activity is feeding. One indicator of quality in food service is food leftover. The high food waste can affect the patient's health. The high food waste will pose a risk of malnutrition in hospitalized patients. The study aimed to analyze the food leftovers in COVID-19 inpatients at the Palembang referral hospital.Methods : This cross-sectional quantitative descriptive study was with a sample of 112 patients selected by purposive sampling in February-May 2021. Data were taken using the Comstock form and then translated in the form of percent leftover food. According to the Minister of Health, the minimum leftover food is less than 25 percent.Results : The results showed that more than 25 percent of the leftover food were 51 respondents; Thirty-three respondents (54.1%) have fully recovered and 28 respondents (45.9%) still in improvement. On the other hand, the leftovers food of less than 25 percent were 51 respondents; Forty respondents (78.4%) have fully cured, and 11 people (21.6%) still in treatments. The analysis of Chi-square test results shows a p-value of 0.013, showing a significant relationship between food waste and the recovery of COVID-19 patients.Conclusion : The food waste of COVID-19 patients in referral hospitals was still relatively high. It is necessary to modify the diet menu to prevent leftovers and speed up the patient's recovery.